STRATEGI MENUMBUHKAN JIWA KEWIRAUSAHAAN DI ERA REVOLUSI INDUSTRI 4.0 - Mamuasi, Rahmat; Habsyi, Faisal Y; Renjaan, Datje (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
The Industrial Revolution 4.0 has transformed the global entrepreneurial paradigm through the integration of digital technology, artificial intelligence, the Internet of Things (IoT), and big data. These changes require the younger generation to have critical, creative, and adaptive thinking skills in response to digital transformation. However, in Indonesia, the entrepreneurial spirit still faces challenges such as low digital literacy, limited access to innovative financing, and weak cross-sector collaboration. This study aims to analyze effective strategies for fostering an entrepreneurial spirit in the Industrial Revolution 4.0 era through a literature review of theories, research results, and the latest national policies. The research method used is a descriptive qualitative approach with a literature review technique of scientific publications from 2019–2025 from various academic sources and official reports. The results of the study indicate that digital entrepreneurship education, strengthening the ecosystem based on the Quadruple Helix model, and the integration of national strategies such as Merdeka Belajar Kampus Merdeka and the National Movement of 1000 Digital Startups are key to building the entrepreneurial character of generation 4.0. In addition, experiential learning, collaborative innovation, and mastery of digital literacy have been shown to increase students' entrepreneurial self-efficacy and creativity. Thus, fostering an entrepreneurial spirit in the digital era not only impacts economic growth but also serves as a fundamental strategy for building the nation's economic independence and resilience towards Digital Indonesia 2045.